Sexual addiction 25 years on: A systematic and methodological review of empirical literature and an agenda for future research. (December 2020) - Grubbs, Joshua B.; Hoagland, K. Camille; Lee, Brinna N.; Grant, Jennifer T.; Davison, Paul; Reid, Rory C.; Kraus, Shane W.
Abstract: In 1998, Gold and Heffner authored a landmark review in Clinical Psychology Review on the topic of sexual addiction that concluded that sexual addiction, though increasingly popular in mental health settings, was largely based on speculation, with virtually no empirical basis. In the more than two decades since that review, empirical research around compulsive sexual behaviors (which subsumes prior research about sexual addiction) has flourished, ultimately culminating in the inclusion of a novel diagnosis of Compulsive Sexual Behavior Disorder in the eleventh edition of the World Health Organization's International Classification of Diseases . The present work details a systematic review of empirical research published between January 1st, 1995 and August 1st, 2020 related to compulsive sexual behaviors, with a specific focus on evaluating the methodologies of that literature. This review yielded 371 papers detailing 415 individual studies. In general, the present review finds that, although research related to compulsive sexual behaviors has proliferated, much of this work is characterized by simplistic methodological designs, a lack of theoretical integration, and an absence of quality measurement. Moreover, the present review finds a virtual absence of high-quality treatment-related research published within this time frame. Implications of these findings for both clinical practice and future research are discussed. Highlights: Research related to sexual addiction and compulsive sexual behaviors has proliferated in recent years. The ICD-11 has elected to include a novel diagnosis of Compulsive Sexual behavior Disorder. A systematic review revealed 415 empirical studies of compulsive sexual behavior in the past 25 years. The majority of studies made use of cross-sectional designs in non-clinical populations. At present, there is almost no empirical basis for the treatment of compulsive sexual behaviors.